2015
DOI: 10.1111/tpj.13049
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplastic thioredoxin m functions as a major regulator of Calvin cycle enzymes during photosynthesis in vivo

Abstract: SUMMARYThioredoxins (Trxs) regulate the activity of various chloroplastic proteins in a light-dependent manner. Five types of Trxs function in different physiological processes in the chloroplast of Arabidopsis thaliana. Previous in vitro experiments have suggested that the f-type Trx (Trx f) is the main redox regulator of chloroplast enzymes, including Calvin cycle enzymes. To investigate the in vivo contribution of each Trx isoform to the redox regulatory system, we first quantified the protein concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 71 publications
(120 reference statements)
8
86
0
Order By: Relevance
“…7 and Fig. S8D), the Trx-z redox state in vivo could not be determined in this study, at least partly due to the low expression level in mature leaves (40,52,56) and the smeared nature of the protein band in the immunoblotting analysis (Figs. S8B and S9C).…”
Section: Cooperative Redox Regulation By the Ftr/trx And Ntrc Pathwaymentioning
confidence: 85%
See 1 more Smart Citation
“…7 and Fig. S8D), the Trx-z redox state in vivo could not be determined in this study, at least partly due to the low expression level in mature leaves (40,52,56) and the smeared nature of the protein band in the immunoblotting analysis (Figs. S8B and S9C).…”
Section: Cooperative Redox Regulation By the Ftr/trx And Ntrc Pathwaymentioning
confidence: 85%
“…What is the significance of chloroplast redox regulation in vivo? To address this question, a number of studies using FTR (48,49), Trx (24,35,(50)(51)(52)(53), or NTRC (15,16,27,54) mutant plants have been reported even during the last few years. Most of these studies focused on the in vivo function of individual redox-mediator proteins.…”
Section: Cooperative Redox Regulation By the Ftr/trx And Ntrc Pathwaymentioning
confidence: 99%
“…S7). The severe growth phenotype also can likely be explained by the defect in plastid redox status, which also controls photosynthetic electron transport, biogenesis of PSII, activation of Calvin cycle enzymes, and starch synthesis in quadruple silencing plants (Michalska et al, 2009;Lepistö et al, 2013;Wang et al, 2013;Okegawa and Motohashi, 2015;Thormählen et al, 2015). Moreover, a double mutant lacking FTRb and NTRC shows a lethal phenotype on soil and is only viable on Murashige and Skoog medium supplemented with Suc.…”
Section: Impact Of Insufficient Content Of Trx Isoforms and Ntrc On Omentioning
confidence: 99%
“…Numerous in vitro and in vivo studies have shown that TRX f and TRX m are required for multiple metabolic processes in chloroplasts, including the Calvin-Benson cycle (Collin et al, 2003;Michelet et al, 2013;Okegawa and Motohashi, 2015;Yoshida et al, 2015), ATP synthesis (Schwarz et al, 1997) and NADPH export (Wolosiuk et al, 1979;Lara et al, 1980), starch metabolism (Fu et al, 1998;Mikkelsen et al, 2005;Seung et al, 2013;Thormählen et al, 2013), fatty acid synthesis (Sasaki et al, 1997), amino acid synthesis (Balmer et al, 2003), and chlorophyll (Chl) synthesis (Ikegami et al, 2007;Luo et al, 2012). Functional genetic analyses have shown that TRX m4 knockout mutants were affected in cyclic electron flow around PSI (Courteille et al, 2013), while a TRX m3 knockout mutant was affected in meristem development (BenitezAlfonso et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation